Predators of the wild - Oxford Scientific Films; Survival Anglia; Time Warner Entertainment Company ([United States] : Oxford Scientific Films : Survival Anglia)
Documentary about life of crocodiles, snakes and bats
vol. 7. Bats.- vol.8. crocodiles and alligators.- vol. 10. snake
Title from cover
Acquisition for KPI (Kelab Pencinta Ilmu)
VCD format
Keywords: Predatory animals; Predation (Biology); Snakes; Crocodiles; Bats